EXPERIENCES OF COVID-19 CONFIRMED PATIENT DURING TREATMENT IN A COVID-19 ISOLATION ROOM: SYSTEMATIC REVIEW - Siregar, Rafika Nur; Tarigan, Mula; Jenny Marlindawani (Jurnal Mal el Hayat, 2024)
Isolation is an unpleasant experience. Changes in the environment, physical isolation from loved ones and boredom cause negative effects that can deteriorate the health of confirmed COVID-19 patients. Explorasi of the experiences of COVID-19 confirmed patient from several research articles aims to help identify the quality of life of patient with confirmed COVID-19. Methods: PRISMA is used for evaluation of research results. SPIDER to formulate research question with the database used by PubMed, CINAHL, Proquest, and Google Scholar. JBI is used to extract analyze data. Results: 6 qualitative studies included in the review. The experiences of 108 COVID-19 confirmed patients with 32 findings resulted in 7 categories based on similarities in meaning and three themes that were synthesized from categories, namely the physiological response of patients with confirmed COVID-19, the psychological response of patients with confirmed COVID-19, and treatment in health fasilities. Conclusion: patients with a confirmed COVID-19 experience various responses while undergoing treatment in the COVID-19 isolation room. In response to this response, patients with confirmed COVID-19 apply different coping mechanisms. In this condition, social support is an important factor in supporting the recovery of patients with confirmed COVID-19. Providing services in the COVID-19 isolation ward needs to rely on and understand the natural condicions of patients with confirmed COVID-19 by developing appropriate intervention strategies.